DISIPLIN WARGA BELAJAR MENGIKUTI PROGRAM KESETARAAN PAKET B DI PKBM LANCANG KUNING PALAS KANAN KECAMATAN RUMBAI - Kiki Elviora Vrismatia Elviora Vrismatia; Jaspar Jas Jaspar Jas; Aswandi Bahar Aswandi Bahar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine the high discipline of the learners in the program equality Paket B at PKBM Lancang Kuning Palas Kecamatan Rumbai Pekanbaru. The question that guides this study is: how high the level of discipline in the learning community program equality Paket B at PKBM Lancang Kuning Palas Kecamatan Rumbai Pekanbaru?. This is a descriptive research, data was collected using a questionnaire instrument shaped 43 point statement. After tested, the questionnaire is valid as for 31 points, and is not valid as for 12 points. Overall the instrument is valid with "rhitung = 0.444 means that validity is quite high. The population in this study were 36 residents who learn paket B. The samples in this study were taken by using the sampling method of total / census with an overall sampling, to determine the number and valid items then can be tested by using a prior questionnaire to the learners paket B in PKBM Lancang Kuning Palas Kecamatan Rumbai Pekanbaru. Based on the findings research obtained disciplinary learning community in PKBM paket B Lancang Kuning Palas Kanan, Pekanbaru is based on the ability of respondents to obey a high level of discipline of 85.76% and a low of 15.12% discipline. Based on the persistency in doing tasks the respondents who are in the high level of discipline of 80.86% and a low of 19.08% discipline. How to dress respondents who rate high at 75.75% discipline and discipline of respondents who rate low of 23.8%. Based on the acceptance the teaching and learning who i a high discipline level of 82% and low of 12%. While using the facilities and infrastructure of respondents who rate high discipline of 95.22% and a low of 4.74% discipline.Key words: discipline, learn people, the program paket B, the center of teaching and activitie learning (PKBM).